Women, work and family in England and France - Clifton, N; Clifton, Naomi (1999)
﻿ This thesis explores some of the individual attitudes and choices which may explain differing patterns in women's work in England and France. Women's work, however, cannot be considered outside the context of their family lives, and there exist important differences between England and France in terms of the structures in place to facilitate the combining of paid work and family commitments. It is proposed that these are related to broader social and economic structures which characterise the countries concerned, and the family and gender roles assumed by them. The question addressed, therefore, is the relationship between work identity and female identity. This is examined by comparing full-time working women, both single and with families, in the two countries. Since the question concerns meanings rather than frequencies, quantitative methods such as surveys are rejected in favour of a triangulated methodology combining repertory grid, Twenty Statements Test and in- depth interview. The results from each of these are reported separately. There is strong convergence within and clear differences between national groups, regardless of marital status. French and English groups are both committed to working, but this takes different forms in the two countries. The French women define themselves equally in terms of work, personal relationships and social lives, with relatively little conflict between them. For the English women, work identity comes first, there is more conflict between work and family roles and more tension in personal relationships. This may partly be accounted for by the English women's greater concern with career progression and personal advancement, which is more likely to conflict with family roles. The findings are related to broader issues of economic, social and family policy, historical factors, religious traditions and attitudes towards gender and equality. These themselves are seen as reflecting more general ideologies in the countries concerned. Finally, there is a consideration of questions raised by the study, and suggestions for further research.